Development of the Dasawisma Group's Organic Vegetable Business Lulu Garden in Lewirato Village, Bima City - Ismunandar Ismunandar; Firmansyah Kusumayadi; M. Inas Riandi; Lalu Muhammad Haikal; Putri Aulia Dinasti (Institut Riset dan Publikasi Indonesia, 2025)
PMP (Community Service for Beginners) activities carried out with partners targeting the Lulu Garden Dasawisma business group in Lewirato Village, Bima City. The problems of this business group are the production process still uses makeshift tools, the lack of group members' skills in business management, suboptimal product marketing and product packaging. Therefore, several solutions are needed related to increasing production capacity through the provision of several adequate production support tools, entrepreneurship and business management seminars and product marketing training and packaging of organic vegetable products, so that these products can attract consumers with a good appearance. This community service uses the planning, implementation and evaluation method. The results of the seminars and training conducted show that the members of this business group have carried out the process of planting and producing organic vegetables better. Group members have also understood the importance of entrepreneurship and business management knowledge in a business. Through the training conducted, group members are able to market their products both offline and online by utilizing social media. In addition, group members are able to package vegetable products according to good standards, namely by using wrapping and logos